2004
DOI: 10.7557/2.24.1.262
|View full text |Cite
|
Sign up to set email alerts
|

Rain more important than windchill for insulation loss in Svalbard reindeer fur

Abstract: Heat transfer through dry and wet Svalbard reindeer (Rangifer tarandus platyrhynchus) summer and winter midback fur samples was studied in a wind tunnel. A light wetting water spray simulated heavy fog, mist or light rain, while heavy soaking simulated heavy rain. Wind velocities ranged from 0 to 10 m . s -1 . Calf fur samples were from June, August and March. Adult fur samples were females from August and March. There was no evidence for increased heat loss from lightly wet fur relative to dry fur. Calm air c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…In the Kerguelen archipelago, snow depth never exceeded 20 cm during our study which limits its negative effect on mouflon (Telfer and Kelsall 1984). That PI, a proxy of the number of days mouflons faced with wet conditions, decreased population growth rate supports the hypothesis of thermoregulation costs through heat loss (Cuyler and Øritsland 2004) for lambs. In our study, windchill (WCI) was not correlated to growth rate but an index combining precipitation and wind could be more relevant.…”
Section: Mouflon and The Climate Of Kerguelensupporting
confidence: 76%
“…In the Kerguelen archipelago, snow depth never exceeded 20 cm during our study which limits its negative effect on mouflon (Telfer and Kelsall 1984). That PI, a proxy of the number of days mouflons faced with wet conditions, decreased population growth rate supports the hypothesis of thermoregulation costs through heat loss (Cuyler and Øritsland 2004) for lambs. In our study, windchill (WCI) was not correlated to growth rate but an index combining precipitation and wind could be more relevant.…”
Section: Mouflon and The Climate Of Kerguelensupporting
confidence: 76%
“…3 mm. Avoidance of rain is not surprising given that wet fur can greatly increase heat loss through evaporation and, to a lesser extent, convection (Gebremedhin and Wu 2001;Cuyler and Øritsland 2004). Although we lacked precipitation data for our red squirrel study, the observed negative effect of relative humidity may have been due to the fact that high humidity is associated with precipitation events.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the projected increase in snowfall in higher elevated and mountainous areas may be harmful for those reindeer spending winters there, as access to lichen, their major winter forage, will be reduced. Moreover, increased precipitation as rain and sleet during calving will drain the newborn calves of heat, since the insulation property of wet pelages is greatly reduced (Cuyler & Øritsland 2004). The calves' limited ability to thermo-regulate due to limited body reserves and high surface area to body mass ratios can lead to reduced neonatal survival.…”
Section: Potential Consequences For Reindeer Husbandry In Norwaymentioning
confidence: 99%